2017
DOI: 10.2147/ott.s146409
|View full text |Cite
|
Sign up to set email alerts
|

Case report of a <em>KIT</em>-mutated melanoma patient with an excellent response to apatinib and temozolomide combination therapy

Abstract: Malignant melanoma is one kind of malignant disease which has high rates of mortality, metastasis, and poor prognosis. The therapeutic landscape is rapidly changing with the development of novel agents in recent decades, such as anti-PD-1 agents, anti-CTLA-4 agents, and BRAF inhibitors. However, since most of these novel agents are very expensive, not all patients can afford them. Apatinib is a novel oral small-molecule tyrosine kinase inhibitor targeting the intracellular domain of vascular endothelial growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“… 8 Besides convincing evidence on gastric cancer treatment, apatinib was also discovered with promising therapeutic effects against diverse tumor types, including breast cancer, non-small-cell lung cancer (NSCLC), hepatocellular carcinoma, melanoma, intrahepatic cholangiocarcinoma, and extrahepatic bile duct cancer. 9 13 However, whether apatinib has an antitumor effect on human pancreatic cancer remains unknown. Chinese traditional herbal medicines have been widely used to treat diseases including cancers.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Besides convincing evidence on gastric cancer treatment, apatinib was also discovered with promising therapeutic effects against diverse tumor types, including breast cancer, non-small-cell lung cancer (NSCLC), hepatocellular carcinoma, melanoma, intrahepatic cholangiocarcinoma, and extrahepatic bile duct cancer. 9 13 However, whether apatinib has an antitumor effect on human pancreatic cancer remains unknown. Chinese traditional herbal medicines have been widely used to treat diseases including cancers.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether Apa can elicit tumor vascular normalization to enhance the effect of chemotherapy remains unclear. Treatment with Apa combined with chemotherapeutic drugs has presented promising therapeutic effects [18][19][20][21]. In the relevant published papers, the synergistic effects of Apa with chemotherapeutic agents have been attributed to the inhibition of multidrug resistance-related efflux transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to promising anti-tumor effects in multiple solid cancers, such as lung cancer [15], colon cancer [16], and nasopharyngeal carcinoma [17], Apa has been involved in some second-line treatments in clinical trials. Currently, there are many successful findings about the combination of Apa with other conventional chemotherapeutic drugs in animal experiments [18,19] and clinical trials [20,21], but direct evidence proving that Apa has a vascular normalization effect from which combination therapies could benefit is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation was found for the first time in a 2-year-old boy affected by cutaneous mastocytosis [ 44 ]. KIT mutation is most frequently observed in acral, mucosal and chronically sun-exposed melanomas [ 45 , 46 ]. In our study, KIT mutation was identified in a TM located in acral site.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, KIT mutation was identified in a TM located in acral site. KIT is another important checkpoint for the targeted therapy in melanomas, since molecules as imatinib, nilotinib and apatinib can affect melanoma cells with KIT mutations [ 44 46 ]. Notably, in our series only two cases were negative for the presence of mutations in the genes analyzed.…”
Section: Discussionmentioning
confidence: 99%